1994
DOI: 10.1111/j.1936-4490.1994.tb00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Meanings of Work and Personal Values of Canadian Anglophone and Francophone Middle Managers

Abstract: The goal of this study was to see if the meaning of work and personal values of Canadian Anglophone public sector male middle‐managers would be more individualist (e. g., more achievement‐oriented in the business world) than those of Francophone managers, who were predicted to be more collectivist (i. e., more concerned with affiliation and family concerns). This was done using a modified version of Triandis's (1972) antecedent‐consequent method. Managers gave logical associations to 21 work and personal value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Lundberg and Peterson (1994) Examines if work goal differences can be attributed to country differences, to organizational, regional or hierarchical levels within local governments across two regions of the US (northeast and Southwest) and Japan 4. Major et al (1994) Work and personal values of Francophone and Anglophone societies of Canada were examined.…”
Section: What We Know: Theorizing Wccrs In Businessmentioning
confidence: 99%
“…Lundberg and Peterson (1994) Examines if work goal differences can be attributed to country differences, to organizational, regional or hierarchical levels within local governments across two regions of the US (northeast and Southwest) and Japan 4. Major et al (1994) Work and personal values of Francophone and Anglophone societies of Canada were examined.…”
Section: What We Know: Theorizing Wccrs In Businessmentioning
confidence: 99%
“…Donolo (2004) argued that there were increasing numbers of Bloc Quebecers aligning with the rest of Canada, and might be dropping their nationalist diatribes and focusing on implicitly Canadian‐value issues. Especially, the study of Major et al (1994) showed the profile similarity between Francophone and Anglophone managers in the individualist‐collectivist understanding of most of the 21 work and personal values. The author argued that this overall similarity was due to the social change that has occurred in Quebec over the past 15 years.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…By contrast, in this paper a broader definition of work ethics is employed, which is considered in its most simplistic way as “a construct compose of two distinct parts: attitudes or values and the behaviours that outwardly reflect these attitudes or values” (McCortney and Engels, 2003, p. 134). A long list of scholars such as Major et al (1994) Dose (1997), Lebo et al (1995), Chew and Putti (1995) and Michael and College (1997) have also employed this broad definition in their work.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with previous findings (Kazemipur, 2006; Kornberg, 1988; Uslaner, 2002) that Quebeckers display less trust toward strangers, which could be attributed to a high proportion of French population in Quebec (Laroche et al, 2004) and its alienation from the other Anglophone regions (Anderson, 2010; Henderson, 2004). Quebec is also a relatively collectivistic society different from the individualistic culture in many other regions of the United States and Canada (Major et al, 1994). Collectivistic societies as such are found to display less trust toward strangers (Watkins and Lui, 1996; Huff and Kelly, 2005).…”
Section: Quantitative Validationmentioning
confidence: 99%